(untitled) (International Seven Journal of Multidisciplinary, 2024)
This article explores the impact of emerging technologies on contemporary education, with the aim of analyzing how these innovations are transforming teaching and learning in schools. The rationale for this study lies in the growing integration of digital tools in the educational environment and the need to understand the challenges and opportunities they bring to the development of effective pedagogical practices. The methodology adopted was of a bibliographic nature, with an extensive review of the existing literature on the subject, including recent and classic studies on the use of technologies in education. Aspects such as the adaptation of teachers to the new role of learning facilitators, the importance of instructional design for the creation of meaningful learning experiences, the issue of equity in access to technologies, and the psychological and emotional impacts of digital teaching were examined. The analysis reveals that while emerging technologies have the potential to revolutionize teaching, their effective implementation depends on an integrated approach that considers not only technical but also pedagogical, ethical, and social aspects. It is concluded that the digital transformation of education requires a profound change in educational paradigms and close collaboration between educators, managers, and public policy makers to ensure that technological innovations contribute to a more inclusive and quality education.